2023
DOI: 10.1038/s41598-023-32467-x
|View full text |Cite|
|
Sign up to set email alerts
|

AI4SeaIce: selecting loss functions for automated SAR sea ice concentration charting

Abstract: For maritime navigation in the Arctic, sea ice charts are an essential tool, which still to this day is drawn manually by professional ice analysts. The total Sea Ice Concentration (SIC) is the primary descriptor of the charts and indicates the fraction of ice in an ocean surface area. Naturally, automating the SIC chart creation is desired. However, the optimal representation of the corresponding machine-learning task is ambivalent and discussed in the community. In this study, we explore the representation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In this study, we refer to several conclusions in their experiments in (Kucik and Stokholm, 2023;Stokholm et al, 2022;Stokholm et al, 2023), including that 1) NERSC noise correction is superior for U-Net model predicting full sea ice covers with little variation in the SAR textures, 2) 11 classes of SIC shows the highest detection accuracies of water and 100% SIC,…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…In this study, we refer to several conclusions in their experiments in (Kucik and Stokholm, 2023;Stokholm et al, 2022;Stokholm et al, 2023), including that 1) NERSC noise correction is superior for U-Net model predicting full sea ice covers with little variation in the SAR textures, 2) 11 classes of SIC shows the highest detection accuracies of water and 100% SIC,…”
mentioning
confidence: 76%
“…More details can be found in the user manuals for the two datasets. Multi-series installments of articles related to AI4Arctic include (Esbensen, 2022;Stokholm et al, 2022;Stokholm et al, 2023;Kucik and Stokholm, 2023). In this paper, we used both the raw and ready-to-train datasets of the latest versions.…”
Section: Ai4arctic Project Datasetmentioning
confidence: 99%
See 2 more Smart Citations
“…Stokholm et al [19] used the AI4Arctic/ASIP v2 (ASID-v2, [11]) benchmark dataset to estimate sea ice concentration developing new variations of U-Net [20], a semantic segmentation architecture. Kucik and Stokholm [21] showed that the choice of loss function can significantly affect the appearance of the sea ice concentration predictions generated by CNN models.…”
Section: Related Workmentioning
confidence: 99%